Ultrasonographically derived caudal vena cava parameters acquired in a standing position and lateral recumbency in healthy, lightly sedated cats: a pilot study. - Hultman TM; Boysen SR; Owen R; Yozova ID (Massey University, 2022)
OBJECTIVES: The aim of this study was to determine the feasibility of ultrasonographically measuring the caudal vena cava (CVC) at the subxiphoid view of healthy, lightly sedated cats in a standing position and lateral recumbency. METHODS: This was a prospective, observational, experimental single-centre study. Twenty healthy research-purposed cats were enrolled. Two trained operators scanned each cat in two positions - standing and lateral recumbency - in a randomised order. CVC diameter was measured at the narrowest diameter during inspiration and at the widest diameter during expiration, at two anatomical locations along the CVC - where the CVC crosses the diaphragm (base) and 2 mm caudal to the diaphragm. The CVC collapsibility index (CVC-CI) was calculated for each site. Normalcy was assessed with a Shapiro-Wilk test. A one-way ANOVA with post-hoc Tukey's test was used to compare inspiratory with expiratory values within and between groups. A paired t-test compared the CVC-CI between groups (P ⩽0.05 indicated statistical significance). Spearman's correlation and Bland-Altman analysis assessed inter-operator variability. RESULTS: All ultrasonographic data passed normalcy and were reported as mean ± SD. When compared with each other, inspiratory and expiratory values were statistically different for position, location and operator (all P <0.0001). There was no statistically significant difference between lateral recumbency or standing position for inspiratory, expiratory and CVC-CI values. Inter-operator variability was substantial, with operator 2 consistently obtaining smaller measurements than operator 1. The mean CVC-CI in lateral recumbency at the base was 24% for operator 1 and 37% for operator 2. For the same site in standing position, CVC-CI was 27% and 41% for operators 1 and 2, respectively. CONCLUSIONS AND RELEVANCE: This pilot study demonstrates that it is possible to ultrasonographically measure the CVC diameter in both lateral recumbency and a standing position in healthy, lightly sedated cats. However, measurements obtained are operator dependent with variability between individuals. Further studies are needed to determine if ultrasonographic CVC assessment will prove helpful in estimating intravascular volume status in cats.
(c) The Author/s
Keywords: Point-of-care ultrasound; intravascular volume status; collapsibility index; cage-side; 0707 Veterinary Sciences